Nanocomposites of graphene oxide and upconversion rare-earth nanocrystals with superior optical limiting performance - Ma, Jan (2013)
Upconversion rare-earth nanomaterials (URENs) possess highly efficient near-infrared (NIR), e.g., 980 nm, laser absorption and unique energy upconversion capabilities. On the other hand, graphene and its derivatives, such as graphene oxide (GO), show excellent performance in optical limiting (OL); however, the wavelengths of currently used lasers for OL studies mainly focus on either 532 or 1064 nm. To design new-generation OL materials working at other optical regions, such as the NIR, a novel nanocomposites, GO–URENs, which combines the advantages of both its components, is synthesized by a one-step chemical reaction. Transmission electron microscopy, X-ray diffraction, infrared spectroscopy, and fluorescence studies prove that the α-phase URENs uniformly attach on the GO surface via covalent chemical bonding, which assures highly efficient energy transfer between URENs and GO, and also accounts for the significantly improved OL performance compared to either GO or URENs. The superior OL effect is also observed in the proof-of-concept thin-film product, suggesting immediate applications in making high-performance laser-protecting products and optoelectronic devices.